Students vs Lecturers: How Should Writing be Taught and Learned? - Yenni Rozimela; Desvalini Anwar; Ririn Ovilia; Ainul Addinna (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
There have been a number of studies investigating the hindrances that students face and their preferences in writing activities. Yet, there raises questions whether all the students’ preferences should be implemented and whether lecturers should comply with all the preferences in order to create an ideal model of teaching and learning writing. Using R & D method, this present study aimed to develop Reading-Based Model of Teaching Academic Writing. This article reports the result of the first stage of the study- the needs analysis.  The data were collected through questionnaires distributed to 127 university students and in-depth interview with four writing lecturers. The students’ voice of their preferences in writing activities with the lecturers’ views on an ideal writing class based on their experiences and knowledge of teaching writing were examined and compared. The results revealed that there were agreements and discrepancy between students’ and lecturers’ perception about stages in writing process, students’ ability to develop ideas, knowledge of text genres, the implementation of writing strategies, and the practice of corrective feedback. This study was expected to shed a light on how writing should be better taught and learned.